Trust and Real Estate Marketing In Ghana: Experience from the Local People - Owusu; Gertrude Agyemang, Alfred (British Journal of Marketing Studies, 2020)
Acquiring a house property is the ultimate goal of every individual in the developed and developing countries. Few scholarly studies have been conducted on customer behaviour towards real estate marketing as well as determining the trust levels of customers that may influence their decision towards real estate marketing in emerging economies. The study employed the qualitative method for data analysis. From the use of in-depth interviews with thirty (30) respondents, this study explores the various causes of customers’ high and low trust levels in engaging in real estate marketing within the Kumasi Metropolis of Ghana. Findings indicated that customers may either opt for building their own house or purchasing a house property from real estate companies for accommodation. The decision to either build or buy a house property are based on customers’ trust in real estate companies to suit the preferences and expectations. Customers place emphasis on convenience, past experiences, credentials and willingness and availability of real estate agents as a positive contributing cause of trust and these are of importance to any customer who attains house ownership through real estate companies. However, themes developed from the interviews were causes of customers’ mistrust towards real estate companies which were the unscrupulous behaviour of real estate markets, fraudulent activities, the emergence of real estate in Ghana as a new sector, inability to build to suit preferences, incomplete information and lack of transparency, delay in possession and lack of maintenance related issues.